(untitled) (Research, Society and Development, 2023)
The bacaba palm (Oenocarpus bacaba Mart.) is a species native to the Amazon, but not endemic, being found naturally in dry land and flooded areas forests in northern Brazil. The objective of this work was to determine the repeatability coefficient and minimum number of evaluations necessary for O. bacaba fruits characters in areas of natural occurrence in the State of Pará, with a view to assisting in the efficient collection process. Forty-four samples of ripe fruit obtained from collection expeditions carried out in three municipalities were used: Baião, Marabá and Terra Santa. Five fruits of each sample were evaluated for eight characters. Estimates of repeatability coefficients were obtained using four methods. Repeatability coefficients ranged from 0.24 for pulp yield per fruit to 0.81 for longitudinal diameter. The longitudinal and transverse diameter characters showed high magnitudes (<0.60). In general, it is believed that samples containing nine fruits are necessary to obtain a coefficient of determination of 90% in seven of the eight characters evaluated in this study.